The Effect of Fiber Waviness on the Residual Stress State and Its Prediction by the Hole Drilling Method in Fiber Metal Laminates: A Global-Local Finite Element Analysis - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Metals)

On the reliability of residual stress measurements in unidirectional carbon fibre reinforced epoxy composites - Magnier, A.; Wu, T.; Tinkloh, Steffen Rainer; Tröster, Thomas; Scholtes, B.; Niendorf, T. (Polymer Testing)

Entwurf netzfreundlicher Synchrongleichrichter mit integriertem Synchronwandler - Henkenius, Carsten

Measurement procedure for acoustic absorption and bulk viscosity of liquids - Claes, Leander; Chatwell, René Spencer; Baumhögger, Elmar; Hetkämper, Tim; Zeipert, Henning; Vrabec, Jadran; Henning, Bernd (Measurement)

Towards a Decision Support System for Cross-Sectoral Energy Distribution Network Planning - Kirchhoff, Jonas; Burmeister, Sascha Christian; Weskamp, Christoph; Engels, Gregor (Energy Informatics and Electro Mobility ICT)
Requirements for energy distribution networks are changing fast due to the growing share of renewable energy, increasing electrification, and novel consumer and asset technologies. Since uncertainties about future developments increase planning difficulty, flexibility potentials such as synergies between the electricity, gas, heat, and transport sector often remain unused. In this paper, we therefore present a novel module-based concept for a decision support system that helps distribution network planners to identify cross-sectoral synergies and to select optimal network assets such as transformers, cables, pipes, energy storage systems or energy conversion technology. The concept enables long-term transformation plans and supports distribution network planners in designing reliable, sustainable and cost-efficient distribution networks for future demands.

Revolten in Gelb und Grün. In 'Rosa und Hannah. Das Blatt wenden' inspiriert Joke J. Hermsen für Krisenzeiten - Lammer, Christina

Designing of thermosetting plastic components for direct screwing - Auslegung von Duroplastbauteilen zur Direktverschraubung - Moritzer, Elmar; Hillemeyer, Johannes; Kramer, M.; Hopmann, C. (Joining Plastics)

Characterization of wood-filled thermoplastic polyurethanes for the injection molding process - Moritzer, Elmar; Richters, Maximilian (Journal of Applied Polymer Science)

Entwicklung der Spritzniettechnik als werkstoffgerechtes Fügeverfahren für hybride Strukturen - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (11. Fügetechnisches Gemeinschaftskolloquium)

Er kommt auf die Korngröße an, Mikrogranulat verbessert die Verteilung feindisperser Füllstoffe in der Direktcompoundierung - Moritzer, Elmar; Jilg, J.; Rücker, Tobias (Kunststoffe)

Eine runde Sache - Schöppner, Volker; Martens, Jan Hendrik (Kunststoffe)

Influence of Fiber Content on the Fiber Dust Formation During Shredding for Mechanical Recycling of Different Glass and Carbon Fiber Reinforced Thermoplastics - Hopp, Matthias; Tölle, Lisa (36th International Conference of Polymer Processing Society (PPS))

Fügeelement angespritzt - Einfluss auf die Verbundfestigkeit zwischen Organoblech und Schraubblindniet untersucht - Moritzer, Elmar; Hillemeyer, Johannes; Lotzin, R. (Kunststoffe)

Effect of Isocyanate Absorption on the Mechanical Properties of Silicone Elastomers in Polyurethane Vacuum Casting - Moritzer, Elmar; Wortmann, M.; Krieger, P.; Hüsgen, B.; Frese, N. (ACS Omega)

INVESTIGATION OF THE PROCESSABILITY OF DIFFERENT HIGHPERFORMANCE MATERIALS IN THE FDM PROCESS WITH REGARD TO THE SHRINKAGE BEHAVIOR - Moritzer, Elmar; Wächter, Julian; Fuhrmann, C. (23rd International Conference Materials)

Lebensdauer vorhersagen? - Schöppner, Volker; Gevers, Karina (K-Zeitung)

Kühlen mit dem Wärmerohr - Moritzer, Elmar (Kunststoffe)

Material Degradation of Polypropylene on the Co-Rotating Twin Screw Extruder - Schöppner, Volker; Altepeter, Matthias; Wanke, Sven (36th International Conference of the Polymer Processing Society (PPS))

Schriftstellerische Inszenierungspraktiken und autofiktionale Schreibreflexionen im Weblog Turmsegler von Benjamin Stein - Willeke, Stephanie (Schreiben, Text, Autorschaft II. Zur Narration und Störung von Lebens- und Schreibprozessen)

Untersuchung der Faserlängenabnahme von kurz- und langglasfaserverstärk-ten Thermoplasten im Spritzgießprozess - Moritzer, Elmar; Bürenhaus, Franziska Isabelle (27. Techomer - Fachtagung über Verarbeitung und Anwendung von Polymeren)